Non-aqueous electrolyte storage element

By employing a separator with specific solvent and electrolyte composition and resistance characteristics, the capacity retention rate of non-aqueous electrolyte storage elements with silicon or tin negative electrodes is enhanced, addressing the volume change issue and maintaining efficient ion conduction.

JP7616063B2Active Publication Date: 2025-01-17GS YUASA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021555786
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-13
Filing Date
2020-06-16
Publication Date
2025-01-17
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

Non-aqueous electrolyte storage elements using silicon or tin as negative electrode active materials experience significant volume changes during charging and discharging, leading to reduced capacity retention rates due to particle cracking and isolation, which affects the separator and impedes lithium ion movement.

Method used

The use of a separator with a thickness expansion coefficient of 10% or more, impregnated with an electrolytic solution composed of ethylene carbonate and ethyl methyl carbonate as solvents and lithium hexafluorophosphate as an electrolyte salt, maintaining a resistance increase relative to pressure change (dR/dP) at 0.15Ω cm²/MPa or less, enhances the capacity retention rate.

Benefits of technology

This configuration improves the capacity retention rate during charging and discharging cycles by minimizing separator compression and current concentration, thereby reducing negative electrode deterioration and maintaining efficient ion conduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616063000003
    Figure 0007616063000003
  • Figure 0007616063000004
    Figure 0007616063000004
  • Figure 0007616063000001
    Figure 0007616063000001
Patent Text Reader

Abstract

One embodiment of the present invention is a nonaqueous electrolyte electricity storage element which is provided with a separator and a negative electrode comprising a negative electrode active material layer that has a thickness expansion ratio by charging of 10% or more, wherein: with respect to the separator that is impregnated with an electrolyte solution for measurement, the absolute value (|dR / dP|) of the ratio of the amount of increase in the resistance (dR) to the amount of increase in the pressure (dP) in a pressurized state is 0.15 Ω∙cm2 / MPa or less; the electrolyte solution for measurement is composed of ethylene carbonate and ethyl methyl carbonate, which serve as solvents, and lithium hexafluorophosphate, which serves as an electrolyte salt; the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70; and the concentration of the lithium hexafluorophosphate is 1.0 mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode body having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, as non-aqueous electrolyte storage elements other than secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] As such nonaqueous electrolyte storage elements, nonaqueous electrolyte storage elements using silicon, tin, or compounds containing these elements as the negative electrode active material have been developed (see Patent Documents 1 to 3). Negative electrode active materials containing silicon or tin have the advantage of having a larger capacity than carbon materials that are widely used as negative electrode active materials. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-053152 A [Patent Document 2] JP 2014-120459 A [Patent Document 3] JP 2002-121023 A Summary of the Invention [Problem to be solved by the invention]

[0005] Negative electrode active materials containing silicon or tin undergo a larger volume change during charging and discharging than carbon materials, and therefore nonaqueous electrolyte storage elements using such negative electrode active materials have a low capacity retention rate during charge-discharge cycles.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a nonaqueous electrolyte storage element that uses a negative electrode active material that undergoes a large volume change during charging and discharging, and that has an improved capacity retention rate during charge and discharge cycles. [Means for solving the problem]

[0007] One aspect of the present invention that has been made to solve the above problems is a battery that includes a separator and a negative electrode having a negative electrode active material layer whose thickness expansion rate upon charging is 10% or more, and in which the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied to the separator impregnated with a test electrolyte is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte solution is composed of ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L.

[0008] Another aspect of the present invention that has been made to solve the above problems is a battery comprising a separator and a negative electrode having a negative electrode active material layer whose thickness expansion rate upon charging is 10% or more, and the separator is impregnated with a test electrolyte, and the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte solution is composed of ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L.

[0009] Another aspect of the present invention is a battery comprising a negative electrode containing silicon or tin and a separator, the separator being impregnated with a test electrolyte, and the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte solution is composed of ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L.

[0010] Another aspect of the present invention is a battery comprising a negative electrode containing silicon or tin and a separator, the separator being impregnated with a test electrolyte, and the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte solution is composed of ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L. Effect of the Invention

[0011] According to the present invention, it is possible to provide a nonaqueous electrolyte storage element using a negative electrode active material that undergoes a large volume change during charging and discharging, and which has an improved capacity retention rate during charge and discharge cycles. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] One aspect of the present invention is a battery comprising a separator and a negative electrode having a negative electrode active material layer whose thickness expansion rate upon charging is 10% or more, and the separator is impregnated with a test electrolyte, and the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte is composed of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) as a solvent and lithium hexafluorophosphate (LiPF6) as an electrolyte salt, the volume ratio of the EC to the EMC is 30:70, and the concentration of the LiPF6 is 1.0 mol / L.

[0014] Another aspect of the present invention is a battery comprising a separator and a negative electrode having a negative electrode active material layer whose thickness expansion rate upon charging is 10% or more, and the separator is impregnated with a test electrolyte, and the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte is composed of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) as a solvent and lithium hexafluorophosphate (LiPF6) as an electrolyte salt, the volume ratio of the EC to the EMC is 30:70, and the concentration of the LiPF6 is 1.0 mol / L.

[0015] The nonaqueous electrolyte storage element (α1, α2) has an improved capacity retention rate in the charge-discharge cycle in a nonaqueous electrolyte storage element using a negative electrode active material that has a large volume change during charging and discharging. The reason for this effect is unclear, but the following is presumed. It is known that in a negative electrode active material that has a large volume change during charging and discharging, the repeated expansion and contraction accompanying charging and discharging easily cause cracking and isolation of particles, which is the cause of the decrease in capacity. However, the inventors presumed that in addition to such cracking and isolation of particles, the expansion of the negative electrode active material layer during charging affects the separator, which in turn affects the decrease in the capacity retention rate. That is, in a conventional nonaqueous electrolyte storage element using a negative electrode active material that has a large volume change, the separator is compressed due to the volume expansion of the negative electrode active material layer during charging, and the ratio of holes that serve as conduction paths for lithium ions and the like in the separator is reduced, making it difficult for lithium ions and the like to move in the thickness direction of the separator. As a result, it is presumed that current concentration occurs in the surface direction of the negative electrode, and deterioration of the negative electrode is accelerated. In contrast, the nonaqueous electrolyte storage elements (α1, α2) use separators with small values ​​(dR / dP) or absolute values ​​(|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when impregnated with the electrolyte solution to be measured, so that the change in the separator resistance is small even when the separator is pressurized with the expansion of the negative electrode active material layer. For this reason, even when the negative electrode active material layer expands, current concentration is unlikely to occur in the surface direction of the negative electrode, and it is presumed that the deterioration of the negative electrode is suppressed and the capacity retention rate is improved. In addition, the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) in the state in which the electrolyte solution for measurement is impregnated is often a positive value in a separator having a three-dimensional mesh structure, but may be a negative value in a separator having a direct pore structure. A separator having a direct pore structure has many continuous pores along the thickness direction of the separator, so the proportion of pores that are blocked by the separator being pressurized is small, while the thickness of the separator is reduced, shortening the distance of the conduction path of lithium ions, etc. For this reason, the resistance of the separator impregnated with the electrolyte solution for measurement may decrease. Therefore, the resistance increase (dR) (dR / dP) relative to the pressure change (dP) may be a negative value.

[0016] The thickness expansion rate of the negative electrode active material layer due to charging is the rate of increase in the average thickness (B) of the negative electrode active material layer during charging (SOC 100%) relative to the average thickness (A) of the negative electrode active material layer during discharging (SOC 0%), and is a value calculated by the following formula (1). Expansion rate (%) = {(BA) / A} × 100 (1) Specifically, the thickness expansion rate of the negative electrode active material layer due to charging is determined by the following measurement. A laminated cell is prepared using the negative electrode for which the thickness expansion rate due to charging is to be measured as the working electrode, and metallic lithium as the counter electrode. The electrolyte used in this laminated cell is a mixed solvent of EC, dimethyl carbonate (DMC) and EMC (volume ratio 30:35:35), LiPF6 as the electrolyte salt, and an electrolyte with a LiPF6 content of 1.0 mol / L. During charging and discharging, the laminated cell is sandwiched between two rectangular stainless steel plates larger than the cell area, and a total of four sets of bolts and nuts arranged in a square are tightened with a torque of 10 cN·m to apply pressure to the laminated cell. A current of 0.1 C and a potential of 0.02 V vs. Li / Li + , constant current constant voltage charging for 15 hours (SOC 100%), current value 0.05C, final potential 2V vs. Li / Li +Each of the negative electrodes subjected to constant current discharge (SOC 0%) is disassembled and the negative electrodes are dried. The thickness of the negative electrode active material layer is then measured with a micrometer. When measuring, the thickness of the negative electrode active material layer is measured at any five points, and the average value is taken as the average thickness. Here, the negative electrode is assumed to have a negative electrode active material layer provided on one side of the negative electrode substrate, and in the case of a negative electrode having a negative electrode active material layer provided on both sides of the negative electrode substrate, the negative electrode active material layer on one side is removed before the test. Note that when the "average thickness" is used for other members, it also means the average value of the thickness measured at any five points.

[0017] In addition, when determining the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP), the pressure applied to the separator impregnated with the electrolyte for measurement is in the thickness direction of the separator. The resistance of the separator impregnated with the electrolyte for measurement in the pressurized state is the resistance in the thickness direction converted into the unit area of ​​the separator (Ω cm 2 ) The resistance is measured in a state where the separator is impregnated with the electrolyte solution for measurement. The electrolyte solution for measurement is used for measuring the dR / dP or |dR / dP| of the separator, and the nonaqueous electrolyte used in the nonaqueous electrolyte storage element of the present invention is not limited to the electrolyte solution for measurement, and any nonaqueous electrolyte can be used.

[0018] Specifically, dR / dP or |dR / dP| is a value measured by the following method. For a laminate in which a separator to be measured, impregnated with the electrolyte solution to be measured, is sandwiched between two sheets of aluminum foil as electrodes to be measured, the resistance between the electrodes to be measured is measured by AC impedance (1MHz-1Hz). The measurement is performed in a state where the laminate is pressurized in the thickness direction (lamination direction). The measurement is performed 1 minute after the start of pressurization, and the value on the real axis where the resistance component on the imaginary axis is near 0 is taken as the resistance value. Pressurization is performed first at 1.6 MPa and then at 4.1 MPa. The measurement is performed at a temperature of 20°C. The resistance at a pressurization of 1.6 MPa is R1, and the resistance at a pressurization of 4.1 MPa is R2, and dR / dP is calculated by the following formula (21), or |dR / dP| is calculated by (22). dR / dP=(R2-R1) / (4.1-1.6) (21) |dR / dP|=|(R2-R1) / (4.1-1.6)| ···(22)

[0019] Another aspect of the present invention is a battery comprising a negative electrode containing silicon or tin and a separator, the separator being impregnated with a test electrolyte, and the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte comprises EC and EMC as a solvent and LiPF6 as an electrolyte salt, the volume ratio of the EC to EMC is 30:70, and the concentration of the LiPF6 is 1.0 mol / L.

[0020] Another aspect of the present invention is a battery comprising a negative electrode containing silicon or tin and a separator, the separator being impregnated with a test electrolyte, and the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.15 Ω cm 2 / MPa or less, the measurement electrolyte comprises EC and EMC as a solvent and LiPF6 as an electrolyte salt, the volume ratio of the EC to EMC is 30:70, and the concentration of the LiPF6 is 1.0 mol / L.

[0021] The nonaqueous electrolyte storage element (β1, β2) is a nonaqueous electrolyte storage element using silicon or tin, which is a negative electrode active material that undergoes a large volume change during charging and discharging, and has an improved capacity retention rate during charge and discharge cycles. The reason why such an effect occurs is unclear, but it is presumed to be for the same reason as in the case of the nonaqueous electrolyte storage element (α1, α2) described above. Silicon or tin may be contained in the negative electrode as simple silicon or tin, or may be contained as a constituent atom in a compound such as an oxide or alloy.

[0022] The separators of the nonaqueous electrolyte storage elements (α1, α2) and the nonaqueous electrolyte storage elements (β1, β2) preferably have an air resistance of 250 sec / 100 mL or less. By using a separator with such low air resistance, current concentration in the surface direction of the negative electrode when the negative electrode active material layer expands is less likely to occur, and the capacity retention rate during charge-discharge cycles can be further improved.

[0023] The air resistance is a value measured by the "Gurley tester method" in accordance with JIS-P8117 (2009) and is the average value of measurements taken at 10 different positions.

[0024] The separators of the nonaqueous electrolyte storage elements (α1, α2) and the nonaqueous electrolyte storage elements (β1, β2) preferably contain a resin having a glass transition point of not more than 200° C. By using such a separator, a sufficient capacity retention rate can be achieved, while a good shutdown function can be achieved in the event of unexpected heat generation, for example.

[0025] The separators of the nonaqueous electrolyte storage elements (α1, α2) and the nonaqueous electrolyte storage elements (β1, β2) preferably contain polyolefin. By using such separators, a sufficient capacity retention rate can be achieved while a good shutdown function can be achieved in the event of unexpected heat generation.

[0026] A nonaqueous electrolyte electricity storage element according to one embodiment of the present invention will be described in detail below.

[0027] <Non-aqueous electrolyte electricity storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte. Hereinafter, a secondary battery will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are stacked with a separator interposed therebetween to form an electrode body. The electrode body may be a wound type in which a long positive electrode, a long negative electrode, and a long separator are wound, or may be a laminated type in which a plurality of positive electrodes, a plurality of negative electrodes, and a plurality of separators are stacked. The electrode body is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a known metal container, a resin container, etc. that are usually used as a container for a secondary battery can be used.

[0028] As described above, the positive electrode, the negative electrode, and the separator are stacked to form an electrode assembly, which is housed in a container. Therefore, the separator is pressurized in the thickness direction due to the expansion of the negative electrode in the thickness direction during charging.

[0029] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0030] The positive electrode substrate has electrical conductivity. "Conductivity" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor deposition film, etc. can be mentioned, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085, A3003, etc. specified in JIS-H-4000 (2014).

[0031] The lower limit of the average thickness of the positive electrode substrate is preferably 5 μm, more preferably 10 μm. The upper limit of the average thickness of the positive electrode substrate is preferably 50 μm, more preferably 40 μm, and even more preferably 30 μm or less. By making the average thickness of the positive electrode substrate equal to or greater than the above lower limit, the strength of the positive electrode substrate can be increased. By making the average thickness of the positive electrode substrate equal to or less than the above upper limit, the energy density per volume of the secondary battery can be increased. For these reasons, it is preferable that the average thickness of the positive electrode substrate is equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0032] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles. The intermediate layer includes, for example, conductive particles such as carbon particles, thereby reducing the contact resistance between the positive electrode substrate and the positive electrode active material layer.

[0033] The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer is usually a layer formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0034] The positive electrode active material can be appropriately selected from known positive electrode active materials that are usually used for lithium ion secondary batteries and the like. As the positive electrode active material, a material capable of absorbing and releasing lithium ions is usually used. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β)]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) Examples of the polyanion compound include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. In the positive electrode active material layer, one of these positive electrode active materials may be used alone, or two or more may be mixed and used.

[0035] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0036] In order to obtain particles of the positive electrode active material or the like in a predetermined shape, a pulverizer, a classifier, or the like is used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is present can also be used. As a classification method, a sieve, a wind classifier, or the like is used as necessary for both dry and wet methods.

[0037] The lower limit of the content of the positive electrode active material in the positive electrode active material layer is preferably 70 mass%, more preferably 80 mass%, and even more preferably 90 mass%. The upper limit of the content of the positive electrode active material is preferably 98 mass%, and more preferably 96 mass%. By setting the content of the positive electrode active material within the above range, the electric capacity of the secondary battery can be increased. The content of the positive electrode active material in the positive electrode active material layer can be set to be equal to or higher than any of the above lower limits and equal to or lower than any of the above upper limits.

[0038] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include graphite; carbon black such as furnace black and acetylene black; metals; and conductive ceramics. The conductive agent may be in the form of powder or fiber. Among these, acetylene black is preferred from the viewpoint of electronic conductivity and coatability.

[0039] The lower limit of the conductive agent content in the positive electrode active material layer is preferably 1 mass %, more preferably 2 mass %. The upper limit of the conductive agent content is preferably 10 mass %, more preferably 5 mass %. By setting the conductive agent content within the above range, the electric capacity of the secondary battery can be increased. For these reasons, the conductive agent content is preferably equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0040] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyolefins (polyethylene, polypropylene, etc.), ethylene-vinyl alcohol copolymers, polymethyl methacrylate, polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyacrylates, polymethacrylates, and polyimides; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0041] The lower limit of the binder content in the positive electrode active material layer is preferably 1 mass %, more preferably 2 mass %. The upper limit of the binder content is preferably 10 mass %, more preferably 5 mass %. By setting the binder content within the above range, the active material can be stably maintained. For these reasons, the binder content is preferably equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0042] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0043] The filler is not particularly limited, and examples of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and aluminosilicate.

[0044] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0045] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer of the negative electrode is not particularly limited and may be the same as that of the intermediate layer of the positive electrode.

[0046] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0047] As the lower limit of the average thickness of the negative electrode substrate, 3 μm is preferable, and 5 μm is more preferable. As the upper limit of the average thickness of the negative electrode substrate, 30 μm is preferable, and 20 μm is more preferable. By setting the average thickness of the negative electrode substrate to be equal to or greater than the above lower limit, the strength of the negative electrode substrate can be increased. By setting the average thickness of the negative electrode substrate to be equal to or less than the above upper limit, the energy density per volume of the secondary battery can be increased. Also, for these reasons, it is preferable that the average thickness of the negative electrode substrate is equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0048] The negative electrode active material layer is usually a layer formed from a so-called negative electrode mixture containing a negative electrode active material. The negative electrode mixture forming the negative electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as required.

[0049] In one embodiment of the present invention, the negative electrode active material layer contains a negative electrode active material containing silicon or tin. Examples of the negative electrode active material containing silicon or tin include a single substance of silicon or tin, and a compound containing silicon or tin. Examples of the compound containing silicon include silicon oxide (SiO x : 0 < x < 2, preferably 0.8 ≤ x ≤ 1.2), silicon nitride, silicon carbide, and the like. Examples of the compound containing tin include tin oxide, tin nitride, tin alloys (such as Sn6Cu5), and the like. In addition, as the negative electrode active material containing silicon or tin, a composite material such as a SiO / Si / SiO2 composite material may be used. As the negative electrode active material containing silicon or tin, a pre-doped one can also be used. That is, for example, the negative electrode active material containing silicon or tin may further contain lithium. The negative electrode active material containing silicon or tin can be used by mixing one kind or two or more kinds. Also, a negative electrode active material containing both silicon and tin may be used.

[0050] The negative electrode active material containing silicon or tin is preferably a negative electrode active material containing silicon (silicon alone or a compound containing silicon). Also, the negative electrode active material containing silicon or tin is preferably an oxide of silicon or tin, more preferably silicon oxide.

[0051] The surface of the negative electrode active material containing silicon or tin is preferably coated with a conductive material such as carbon. By using such a form of the negative electrode active material, the electronic conductivity of the negative electrode active material layer can be improved. When the negative electrode active material containing silicon or tin is in the form of particles coated with a conductive material, the mass ratio of the conductive material to the total amount of the negative electrode active material containing silicon or tin and the conductive material coating it is preferably, for example, 1 mass% or more and 10 mass% or less, more preferably 2 mass% or more and 5 mass% or less.

[0052] The shape of the negative electrode active material containing silicon or tin is not particularly limited, and may be plate-like, tubular, etc., but is preferably particulate. The average particle size of the negative electrode active material containing silicon or tin is preferably 0.1 μm or more and 20 μm or less. By setting the average particle size of the negative electrode active material containing silicon or tin to the above lower limit or more, the production or handling of the negative electrode active material containing silicon or tin becomes easy. By setting the average particle size of the negative electrode active material containing silicon or tin to the above upper limit or less, the expansion of the negative electrode active material layer is suppressed, and the capacity retention rate in the charge and discharge cycle is improved.

[0053] The lower limit of the content of the negative electrode active material containing silicon or tin in the entire negative electrode active material is preferably 1 mass%, more preferably 2 mass%, further preferably 4 mass%, and even more preferably 10 mass% in some cases. By making the content of the negative electrode active material containing silicon or tin equal to or more than the above lower limit, the discharge capacity of the secondary battery can be increased. On the other hand, the upper limit of the content of the negative electrode active material containing silicon or tin in the entire negative electrode active material may be, for example, 100 mass%, but may be preferably 90 mass%, more preferably 80 mass%, further preferably 60 mass%, and even more preferably 40 mass% in some cases. By making the content of the negative electrode active material containing silicon or tin equal to or less than the above upper limit, the capacity retention rate of the secondary battery can be further increased. The content of the negative electrode active material containing silicon or tin in the entire negative electrode active material can be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0054] The negative electrode active material layer preferably further contains a carbon material as a negative electrode active material. Examples of the carbon material include graphite and non-graphitic carbon, and graphite is preferred. By containing such a carbon material as the negative electrode active material, the capacity retention rate of the secondary battery is further increased.

[0055] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0056] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. The crystallite size Lc of non-graphitic carbon is usually 0.80 to 2.0 nm. Examples of non-graphitic carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitic carbon include materials derived from resins, materials derived from petroleum pitch, and materials derived from alcohols.

[0057] The "discharged state" in the definition of graphite and non-graphitic carbon refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the redox potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the redox potential of Li. In other words, the open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0058] The lower limit of the carbon material content in the entire negative electrode active material may be, for example, 0 mass%, but may be preferably 10 mass%, more preferably 20 mass%, further preferably 40 mass%, and even more preferably 60 mass%. By setting the carbon material content to the above lower limit or more, it is possible to further increase the capacity maintenance rate of the secondary battery. On the other hand, the upper limit of this content is preferably 99 mass%, more preferably 98 mass%, further preferably 96 mass%, and even more preferably 90 mass%. By setting the carbon material content to the above upper limit or less, it is possible to increase the content of the negative electrode active material containing silicon or tin, and to increase the discharge capacity of the secondary battery. The content of the carbon material in the entire negative electrode active material can be set to any of the above lower limits or more and any of the above upper limits or less.

[0059] The negative electrode active material may further include a known negative electrode active material that is normally used in lithium ion secondary batteries, etc., other than the negative electrode active material containing silicon or tin and the carbon material. Examples of such other negative electrode active materials include titanium oxide and polyphosphate compounds. However, the lower limit of the total content of the negative electrode active material containing silicon or tin and the carbon material in the entire negative electrode active material is preferably 90 mass%, more preferably 99 mass%. On the other hand, the upper limit of this total content may be 100 mass%. In this way, the effect of the present invention is more fully achieved by using only the negative electrode active material containing silicon or tin, or by using only the negative electrode active material containing silicon or tin and the carbon material as the negative electrode active material.

[0060] The lower limit of the content of the negative electrode active material in the negative electrode active material layer is preferably 70 mass%, more preferably 80 mass%, and even more preferably 90 mass%. The upper limit of the content of the negative electrode active material is preferably 98 mass%, and more preferably 97 mass%. By setting the content of the negative electrode active material in the above range, the electric capacity of the secondary battery can be increased.

[0061] The optional components in the negative electrode active material layer, such as a conductive agent, a binder, a thickener, and a filler, may be the same as those in the positive electrode active material layer. The content of each of these optional components in the negative electrode active material layer may be within the range described as the content of each of these optional components in the positive electrode active material, etc.

[0062] Among the above-mentioned binders, fluororesin, polyacrylate, polymethacrylate, styrene butadiene rubber, elastomer, etc. are preferably used as the binder in the negative electrode active material layer. However, since these resins are relatively flexible, the negative electrode active material containing silicon or tin is likely to expand during charging. Therefore, when the binder in the negative electrode active material layer is these resins, the advantages of the present invention are more effectively achieved.

[0063] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0064] The lower limit of the average thickness of the negative electrode active material layer during discharge (SOC 0%) is, for example, preferably 10 μm, more preferably 20 μm. By making the average thickness of the negative electrode active material layer during discharge (SOC 0%) equal to or greater than the above lower limit, the discharge capacity can be increased. The upper limit of the average thickness is preferably 300 μm, more preferably 200 μm. The average thickness of the negative electrode active material layer during discharge (SOC 0%) may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0065] In one embodiment of the present invention, the expansion rate of the negative electrode active material layer is 10% or more. The lower limit of this expansion rate may be 15% or 18%. When the present invention is applied to a nonaqueous electrolyte storage element having a negative electrode active material layer with such a large expansion rate, the advantage of the present invention, that is, the improvement of the capacity maintenance rate in the charge-discharge cycle, can be fully enjoyed. The upper limit of this expansion rate may be, for example, 300%, 150%, or 80%. The expansion rate may be equal to or greater than any of the lower limits and equal to or less than any of the upper limits.

[0066] An example of an anode active material layer having an expansion rate of 10% or more is an anode active material layer containing the above-mentioned silicon or tin-containing anode active material. In addition, an anode active material layer using aluminum, magnesium, germanium, etc. as the anode active material can also have an expansion rate of 10% or more. A suitable form of an anode active material layer having an expansion rate of 10% or more is the same as the form of the anode active material layer containing the above-mentioned silicon or tin-containing anode active material. Note that the expansion rate tends to increase as the content of the silicon or tin-containing anode active material in the anode active material layer and the average thickness of the anode active material layer increase.

[0067] In one embodiment of the present invention, the expansion rate of the negative electrode active material layer based on the uncharged state (never charged) is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more. Even when the present invention is applied to a non-aqueous electrolyte storage element having a negative electrode active material layer with a large expansion rate based on the uncharged state, the advantage of the present invention, that is, the improvement of the capacity retention rate in the charge and discharge cycle, can be fully enjoyed. The upper limit of the expansion rate based on the uncharged state may be, for example, 300%, 150%, or 80%. Examples of the negative electrode active material layer with an expansion rate of 30% or more based on the uncharged state are the same as the above-mentioned examples of the negative electrode active material layer with an expansion rate of 10% or more.

[0068] The expansion coefficient based on the uncharged state of the negative electrode active material layer is the rate of increase in the average thickness (B) of the negative electrode active material layer during charging (SOC 100%) relative to the average thickness (A') of the negative electrode active material layer when uncharged (never charged), and is a value calculated by the following formula (1'). Expansion rate based on uncharged state (%) = {(B-A') / A'} × 100 (1')

[0069] (Separator) The separator usually has a sheet-like substrate having a porous property. The substrate of the separator is usually made of a resin. The separator may be composed of only the substrate, or may further have an inorganic layer laminated on the substrate. The separator is infiltrated with a non-aqueous electrolyte. The separator separates the positive electrode and the negative electrode, and holds the non-aqueous electrolyte between the positive electrode and the negative electrode.

[0070] When the separator is impregnated with the electrolyte for measurement and pressure is applied and the resistance is measured, the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) is 0.15 Ω cm 2 / MPa. The upper limit of the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) is 0.12 Ω cm2 / MPa is preferred, and 0.10 Ω cm 2 / MPa is more preferable, and 0.08 Ω cm 2 / MPa is more preferable, and 0.05 Ω cm 2 / MPa is even more preferable, and 0.02 Ω cm 2 / MPa is even more preferable. The capacity retention rate is further increased by the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) being equal to or less than the above upper limit. The lower limit of the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) is 0 Ω cm 2 / MPa, but 0.005 Ω cm 2 / MPa is preferred, and 0.01 Ω cm 2 / MPa may be more preferable. By setting the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) to be equal to or greater than the above lower limits, the risk of insufficient follow-up to changes in electrode thickness can be reduced. The absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits. The lower limit of the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) may be a negative value, and may be less than -0.15 Ω cm 2 / MPa, -0.12 Ω cm 2 / MPa is preferred, -0.10 Ω cm 2 / MPa is more preferable, -0.08 Ω cm 2 / MPa is more preferable, and -0.05 Ω cm 2 / MPa is even more preferable, and -0.02 Ω cm 2 / MPa is most preferred.

[0071] The value (dR / dP) and absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) are adjusted by the separator material, the degree of porosity (porosity and air resistance), etc. In addition, in the case of a hard separator, it is considered that it is difficult to deform even when pressurized, and the conductive path of lithium ions, etc. is difficult to be crushed. Therefore, for example, even if the air resistance is the same, it is considered that the harder the separator is, the smaller the value (dR / dP) and absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) tends to be. However, for example, even if the separator is made of the same polyethylene, the hardness varies depending on the polymerization degree, crystallization degree (density), etc. of the polyethylene, and separators formed of resins with relatively high polymerization degree and crystallization degree tend to be hard.

[0072] When measuring the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP), the resistance (R2) when pressurized with 4.1 MPa is, for example, 0.02 Ω cm 2 More than 0.3Ω cm 2 If the material has a resistance in this range under high pressure, it can exhibit sufficient ion conductivity and is more useful as a separator.

[0073] The upper limit of the air resistance of the separator may be, for example, 400 seconds / 100 mL, preferably 300 seconds / 100 mL, more preferably 250 seconds / 100 mL, and even more preferably 200 seconds / 100 mL. The lower limit of the air resistance may be, for example, 1 second / 100 mL, 10 seconds / 100 mL, or 50 seconds / 100 mL. The air resistance may be equal to or greater than any of the lower limits and equal to or less than any of the upper limits.

[0074] By setting the air permeability resistance of the separator to the above upper limit or less, the capacity retention rate tends to be improved. However, as shown in the examples described later, when the air permeability resistance is in the range of, for example, 200 seconds / 100 mL or less, the correlation between the air permeability resistance and the capacity retention rate is low. It is considered that there is a limit to the improvement of the capacity retention rate by only adjusting the parameters that depend on the porosity of the separator, such as the air permeability resistance.

[0075] The substrate of the separator may be, for example, a woven fabric, a nonwoven fabric, or a microporous membrane. Among these, nonwoven fabric and microporous membrane are preferred, and microporous membrane is more preferred. Microporous membranes have advantages such as high strength. Nonwoven fabrics have advantages such as high liquid retention.

[0076] Resins constituting the substrate of the separator are not particularly limited, but examples thereof include polyolefins, polyesters, polyimides, polyamides (aromatic polyamides, aliphatic polyamides, etc.). Polyolefins also include copolymers of olefins with other monomers. Examples of polyolefins include polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, polyolefin derivatives such as chlorinated polyethylene, ethylene-propylene copolymers, etc.

[0077] Among these resins, polyolefin, polyester and aliphatic polyamide are preferred, polyolefin is more preferred, and PE, PP and ethylene-propylene copolymer are further preferred. These resins have a relatively low glass transition point and can exhibit a good shutdown function in the event of unexpected heat generation.

[0078] From the viewpoint of such a shutdown function, the upper limit of the glass transition point of the resin contained in the separator substrate is preferably 200° C., more preferably 100° C., and further preferably 30° C. The lower limit of the glass transition point may be, for example, −200° C. or −150° C. The glass transition point may be equal to or higher than any of the lower limits and equal to or lower than any of the upper limits.

[0079] The "glass transition point" of a resin can be determined by differential scanning calorimetry (DSC). Specifically, a differential scanning calorimeter (Rigaku Thermo plus DSC8230) is used, with the heating rate set at 10°C / min. The temperature at which the baseline shifts is taken as the glass transition point. For measurements below room temperature, liquid nitrogen is used to create a low-temperature atmosphere.

[0080] The lower limit of the average thickness of the separator substrate is preferably 5 μm, more preferably 10 μm. The upper limit of this average thickness is preferably 50 μm, more preferably 30 μm. By making the average thickness of the separator substrate equal to or greater than the above lower limit, it is possible to reliably prevent short circuits between the positive electrode and the negative electrode. In addition, by making the average thickness of the separator substrate equal to or less than the above upper limit, it is possible to increase the energy density. The above average thickness may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0081] The inorganic layer of the separator may contain, for example, inorganic particles and a binder.

[0082] Examples of inorganic particles include oxides such as alumina, silica, zirconia, titania, magnesia, ceria, yttria, zinc oxide, and iron oxide, nitrides such as silicon nitride, titanium nitride, and boron nitride, silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, and magnesium silicate. Among these, alumina, silica, or titania particles are preferred.

[0083] Specific examples of the binder for the inorganic layer of the separator include those exemplified as the binder for the positive electrode active material layer described above.

[0084] The lower limit of the average thickness of the inorganic layer of the separator is preferably 1 μm, more preferably 2 μm. On the other hand, the upper limit of the average thickness of the inorganic layer is preferably 20 μm, more preferably 10 μm, and even more preferably 6 μm. By making the average thickness of the inorganic layer equal to or greater than the above lower limit, the heat resistance of the separator can be improved. By making the average thickness of the inorganic layer equal to or less than the above upper limit, the energy density can be increased. The above average thickness may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0085] The lower limit of the average thickness of the separator is preferably 5 μm, more preferably 10 μm. The upper limit of this average thickness is preferably 50 μm, more preferably 30 μm. By making the average thickness of the separator equal to or greater than the above lower limit, it is possible to reliably prevent short circuits between the positive electrode and the negative electrode. In addition, by making the average thickness of the separator equal to or less than the above upper limit, it is possible to increase the energy density. The above average thickness may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0086] (Non-aqueous electrolyte) The non-aqueous electrolyte is not particularly limited, and may be a known non-aqueous electrolyte that is generally used in a general non-aqueous electrolyte secondary battery (electric storage element). The non-aqueous electrolyte may be, for example, a non-aqueous electrolyte solution containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Other additives may be added to the non-aqueous electrolyte.

[0087] The non-aqueous solvent may be a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, and nitriles. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a cyclic carbonate and a chain carbonate in combination. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is not particularly limited, but is preferably 5:95 or more and 50:50 or less.

[0088] Examples of the cyclic carbonate include EC, propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, and the like. Of these, EC, PC, and FEC are preferred.

[0089] Examples of the chain carbonate include DMC, EMC, diethyl carbonate (DEC), and diphenyl carbonate, and among these, EMC is preferred.

[0090] The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte for a storage element, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.

[0091] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a fluorohydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0092] The lower limit of the content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / L, more preferably 0.3 mol / L, even more preferably 0.5 mol / L, and particularly preferably 0.7 mol / L. On the other hand, the upper limit is not particularly limited, but is preferably 2.5 mol / L, more preferably 2 mol / L, and even more preferably 1.5 mol / L. In addition, the content of the electrolyte salt is preferably equal to or greater than any of the lower limits and equal to or less than any of the upper limits.

[0093] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The nonaqueous electrolyte storage element according to one embodiment of the present invention can be manufactured by a known method. The nonaqueous electrolyte storage element can be manufactured by a manufacturing method including, for example, preparing a positive electrode, preparing a negative electrode, stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween to form an electrode body in which the electrodes are alternately stacked, housing the positive electrode and the negative electrode (electrode body) in a container, and injecting a nonaqueous electrolyte into the container. After these steps, the inlet is sealed to obtain a nonaqueous electrolyte storage element. The separator may be manufactured by a known method, or a commercially available product may be used.

[0094] <Other embodiments> The present invention is not limited to the above-described embodiment, and can be embodied in various modified and improved forms in addition to the above-described forms. For example, the positive electrode or the negative electrode does not need to have an intermediate layer.

[0095] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but the nonaqueous electrolyte storage element may be another type of nonaqueous electrolyte storage element, such as a capacitor (electric double layer capacitor, lithium ion capacitor, etc.).

[0096] FIG. 1 is a schematic diagram of a rectangular nonaqueous electrolyte storage element 1 (nonaqueous electrolyte secondary battery) which is one embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure is a see-through view of the inside of a container. In the nonaqueous electrolyte storage element 1 shown in FIG. 1, an electrode body 2 is housed in a container 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material and a negative electrode having a negative electrode active material with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 5'.

[0097] The configuration of the nonaqueous electrolyte storage element according to the present invention is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery (rectangular battery), and a flat battery. The present invention can also be realized as an electricity storage device including a plurality of the nonaqueous electrolyte storage elements. One embodiment of the electricity storage device is shown in FIG. 2. In FIG. 2, an electricity storage device 30 includes a plurality of electricity storage units 20. Each electricity storage unit 20 includes a plurality of nonaqueous electrolyte storage elements 1. The electricity storage device 30 can be mounted as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). EXAMPLES

[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0099] [Example 1] (Preparation of positive electrode) In terms of mass ratio, the positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture paste was prepared containing O2), acetylene black (AB), and PVDF in a ratio of 94:3:3 (solid equivalent) and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to an aluminum foil (average thickness 20 μm) as a positive electrode substrate and dried to obtain a positive electrode.

[0100] (Preparation of negative electrode) The silicon oxide (SiO) particles, graphite, and AB were mixed in a mass ratio of 20:78:2 to obtain a mixture containing a negative electrode active material (silicon oxide and graphite). A negative electrode mixture paste was prepared containing the above mixture:sodium polyacrylate (PAANa) in a mass ratio of 95:5 (solid equivalent) and using water as a dispersion medium. This negative electrode mixture paste was applied to copper foil (average thickness 20 μm) as a negative electrode substrate and dried to obtain a negative electrode. The silicon oxide particles used were particles in which the surface of particulate silicon oxide was coated with carbon, which is a conductive material (carbon content 2.5% by mass). The expansion coefficient of the negative electrode active material layer of the obtained negative electrode was measured by the method described above. The average thickness in the uncharged state (before initial charge / discharge) was 44 μm, the average thickness during charging (SOC 100%) was 63 μm, and the average thickness during discharging (SOC 0%) was 53 μm. The expansion coefficient based on the above formula (1) was 19%, and the expansion coefficient based on the above formula (1') with respect to the uncharged state was 43%.

[0101] (Preparation of non-aqueous electrolyte) A non-aqueous electrolyte was prepared by mixing FEC and EMC in a volume ratio of 10:90 into a non-aqueous solvent and then mixing LiPF6 as an electrolyte salt at a content of 1.0 mol / L.

[0102] (Separator) As the separator, a separator (average thickness 25 μm; no inorganic layer) made of a microporous base material made of polypropylene (glass transition point about 0° C.) was prepared. The value (dR / dP) and absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) in this separator impregnated with the measurement electrolyte were measured by the above-mentioned method. Specifically, the following was performed. First, a laminate of aluminum foil as a measurement electrode and a separator to be measured was prepared in the following manner. Two sheets of aluminum foil (average thickness 20 μm) were prepared, each having a flat portion of 30 mm×40 mm and an ear portion of 10 mm×10 mm connected to one end of the flat portion, with an aluminum tab lead welded to the ear portion. The above two sheets of aluminum foil were laminated on both sides of a separator with a size of 34 mm×53 mm so as not to contact each other, and pasted together with polyphenylene sulfide tape to form a laminate. This laminate was housed in an exterior body made of an aluminum metal resin composite film, and the upper part (the side of the ear part) was heat-sealed. Then, the above-mentioned electrolyte for measurement was injected from the lower part of the exterior body. After that, after degassing under reduced pressure, the lower part of the exterior body was sealed under reduced pressure by heat welding to obtain a measurement cell. Both sides of the obtained measurement cell were sandwiched between two silicone rubber sheets (35 mm x 45 mm, thickness 2 mm), and further sandwiched between two stainless steel plates (55 mm x 55 mm), and pressure was applied in the thickness direction (lamination direction) using a hydraulic press. In the pressurized state, the resistance between the above-mentioned measurement electrodes was measured by AC impedance (1 MHz-1 Hz). The measurement was performed 1 minute after the start of pressurization, and the value on the real axis where the resistance component of the imaginary axis was near 0 was taken as the resistance value. Pressurization was first performed at 1.6 MPa, and then at 4.1 MPa. The above measurement was performed at a temperature of 20°C. The resistance when the pressure was 1.6 MPa was R1, and the resistance when the pressure was 4.1 MPa was R2. dR / dP was calculated using the following formula (21) and |dR / dP| was calculated using (22). dR / dP=(R2-R1) / (4.1-1.6) (21) |dR / dP|=|(R2-R1) / (4.1-1.6)| ···(22) dR / dP is -0.048 Ω cm 2 / MPa, and |dR / dP| is 0.048 Ω cm 2The air resistance of the separator was 185 seconds / 100 mL.

[0103] (Preparation of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with the separator interposed therebetween to prepare an electrode assembly, which was then housed in a case made of a metal resin composite film, and the nonaqueous electrolyte was poured into the case, which was then sealed by thermal welding to obtain the nonaqueous electrolyte storage element (secondary battery) of Example 1.

[0104] [Example 2, Comparative Examples 1 and 2] The nonaqueous electrolyte storage elements of Example 2 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that separators having the air permeability resistance and the values ​​(dR / dP) or absolute values ​​(|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) shown in Table 1 were used.

[0105] [Reference example 1] A negative electrode having a negative electrode active material layer containing only graphite as the negative electrode active material was obtained in the same manner as in the preparation of the negative electrode of Example 1, except that a negative electrode mixture paste containing graphite:SBR:CMC in a mass ratio of 98:1:1 (solids equivalent) and water as a dispersion medium was used. The expansion coefficient of the negative electrode active material layer of the obtained negative electrode was measured by the method described above. The average thickness in the uncharged state (before initial charge / discharge) was 71 μm, the average thickness during charging (SOC 100%) was 90 μm, and the average thickness during discharging (SOC 0%) was 84 μm. The expansion coefficient based on the above formula (1) was 7%, and the expansion coefficient based on the above formula (1') with respect to the uncharged state was 27%.

[0106] [evaluation] (Initial charge / discharge) The obtained nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 were initially charged and discharged in the following manner. At 25°C, constant current constant voltage charging was performed with a charging current of 0.1C, a charging end voltage of 4.2V, and a total charging time of 13 hours. Then, constant current discharging was performed with a discharging current of 0.2C and a discharging end voltage of 2.5V. Then, constant current constant voltage charging was performed with a charging current of 0.2C, a charging end voltage of 4.2V, and a total charging time of 8 hours. Then, constant current discharging was performed with a discharging current of 0.2C and a discharging end voltage of 2.5V. Then, constant current constant voltage charging was performed with a charging current of 0.2C, a charging end voltage of 4.2V, and a total charging time of 8 hours. Then, constant current discharging was performed with a discharging current of 1.0C and a discharging end voltage of 2.5V. A rest period of 10 minutes was provided between charging and discharging.

[0107] (Charge-discharge cycle test) After the initial charge and discharge, the nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to a charge and discharge cycle test as follows. In a thermostatic chamber at 25°C, constant current and constant voltage charging was performed with a charge current of 1.0C and a charge cut-off voltage of 4.2V. The charge was terminated until the charge current reached 0.05C. After a rest period of 10 minutes, constant current discharge was performed with a discharge current of 1.0C and a discharge cut-off voltage of 2.5V, followed by a rest period of 10 minutes. This charge and discharge was repeated 100 times. The ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle in this charge and discharge cycle test was determined as the capacity retention rate. The capacity retention rates of the nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Table 1.

[0108] [Example 3] (Preparation of positive electrode) In terms of mass ratio, the positive electrode active material (LiNi 1 / 2 Co 1 / 5 Mn 3 / 10 A positive electrode mixture paste was prepared by mixing O2):AB:PVDF in a ratio of 93:3.5:3.5 (solid equivalent) and using NMP as a dispersion medium. This positive electrode mixture paste was applied to an aluminum foil (average thickness 15 μm) as a positive electrode substrate and dried to obtain a positive electrode.

[0109] (Preparation of negative electrode) The silicon oxide (SiO) particles and graphite were mixed at a mass ratio of 5:95 to obtain a mixture of negative electrode active materials (silicon oxide and graphite). A negative electrode mixture paste was prepared containing the above mixture:SBR:CMC at a mass ratio of 97:2:1 (solids equivalent) and using water as a dispersion medium. This negative electrode mixture paste was applied to copper foil (average thickness 10 μm) as a negative electrode substrate and dried to obtain a negative electrode. The silicon oxide particles used were particles in which the surface of particulate silicon oxide was coated with carbon, which is a conductive material (carbon content 5% by mass). The expansion coefficient of the negative electrode active material layer of the obtained negative electrode was measured by the method described above. The average thickness in the uncharged state (before initial charge / discharge) was 76 μm, the average thickness during charging (SOC 100%) was 103 μm, and the average thickness during discharging (SOC 0%) was 85 μm. The expansion coefficient based on the above formula (1) was 21%, and the expansion coefficient based on the above formula (1') with respect to the uncharged state was 36%.

[0110] (Preparation of non-aqueous electrolyte) A non-aqueous electrolyte was prepared by mixing EC, PC, and EMC in a volume ratio of 25:5:70 into a non-aqueous solvent and then mixing LiPF6 as an electrolyte salt at a content of 1.0 mol / L.

[0111] (Separator) A separator (average thickness 24 μm) consisting of a microporous substrate (average thickness 20 μm) made of polyethylene (glass transition point approximately -125°C) and an inorganic layer (average thickness 4 μm) was prepared. The value (dR / dP) and absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) in this separator impregnated with the measurement electrolyte were measured using the method described above. The dR / dP was 0.013 Ω cm 2 / MPa, and |dR / dP| is 0.013 Ω cm 2 The air permeability resistance of the separator was 150 seconds / 100 mL.

[0112] (Preparation of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with the separator interposed therebetween to produce an electrode assembly, which was then housed in a case made of a metal resin composite film, and the nonaqueous electrolyte was poured into the case, which was then sealed by thermal welding to obtain a nonaqueous electrolyte storage element (secondary battery) of Example 3.

[0113] [Examples 4 to 6] Each of the nonaqueous electrolyte storage elements of Examples 4 to 6 was obtained in the same manner as in Example 3, except that the separators shown in Table 2 were used.

[0114] [evaluation] (Initial charge / discharge) The obtained nonaqueous electrolyte storage elements of Examples 3 to 6 were initially charged and discharged in the following manner. At 25°C, constant current constant voltage charging was performed with a charging current of 0.2C, a charging end voltage of 4.25V, and a total charging time of 7 hours. Then, constant current discharging was performed with a discharging current of 0.2C and a discharging end voltage of 2.75V. Then, constant current constant voltage charging was performed with a charging current of 0.7C, a charging end voltage of 4.25V, and a total charging time of 3 hours. Then, constant current discharging was performed with a discharging current of 1.0C and a discharging end voltage of 2.75V. Then, constant current constant voltage charging was performed with a charging current of 0.7C, a charging end voltage of 4.25V, and a total charging time of 3 hours. Then, constant current discharging was performed with a discharging current of 1.0C and a discharging end voltage of 2.75V. A rest period of 10 minutes was provided between charging and discharging.

[0115] (Charge-discharge cycle test) After the initial charge and discharge, the nonaqueous electrolyte storage element of Examples 3 to 6 was subjected to a charge and discharge cycle test as follows. In a thermostatic chamber at 45°C, constant current and constant voltage charging was performed at a charge current of 0.7C and a charge cut-off voltage of 4.25V. The charge was terminated until the charge current reached 0.01C. After a rest period of 10 minutes, constant current discharge was performed at a discharge current of 1.0C and a discharge cut-off voltage of 2.75V, followed by a rest period of 10 minutes. This charge and discharge was repeated 150 times. The ratio of the discharge capacity at the 150th cycle to the discharge capacity at the 1st cycle in this charge and discharge cycle test was determined as the capacity retention rate. The capacity retention rates of the nonaqueous electrolyte storage elements of Examples 3 to 6 are shown in Table 2.

[0116] [Table 1]

[0117] [Table 2]

[0118] As shown in Table 1, the dR / dP or |dR / dP| value of the separator (separator impregnated with the measurement electrolyte) is 0.15 Ω cm 2 The nonaqueous electrolyte storage elements of Examples 1 and 2, in which the air resistance is 0.1 to 1.0 MPa or less, have a high capacity retention rate. When the air resistance of the separator is taken into consideration, the capacity retention rate tends to decrease when the air resistance is too high as in Comparative Example 1, but the result does not show that the smaller the air resistance, the better the capacity retention rate, as in the relationship between Example 1 and Comparative Example 2. In other words, there is a limit to improving the capacity retention rate by adjusting the degree of porosity, such as the air resistance of the separator, and it can be seen that the capacity retention rate can be further improved by using a separator designed or selected based on the value (dR / dP) or absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP).

[0119] The charge-discharge cycle tests in each Example in Table 2 were conducted under stricter conditions in terms of temperature, number of cycles, etc. than those in each Example and Comparative Example in Table 1. As shown in Table 2, the dR / dP or |dR / dP| value of the separator (separator impregnated with the measurement electrolyte) was 0.05 Ω cm 2 / MPa or less, and further, 0.02 Ω cm 2 / MPa or less, the capacity retention rate is increased even in severe charge-discharge cycle tests. [Industrial Applicability]

[0120] The present invention can be applied to nonaqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, automobiles, industrial devices, and the like. [Explanation of symbols]

[0121] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 4' Positive lead 5 Negative terminal 5' Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. a negative electrode having a negative electrode active material layer whose thickness expansion rate due to charging is 10% or more, and a separator; In the separator impregnated with the test electrolyte, the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure was applied was 0.15 Ω cm 2 / MPa or less, The measurement electrolyte solution contains ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L, The nonaqueous electrolyte electricity storage element, wherein the separator has a shutdown function.

2. a negative electrode having a negative electrode active material layer whose thickness expansion rate due to charging is 10% or more, and a separator; In the separator impregnated with the test electrolyte, the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.005 Ω·cm 2 / MPa or more and 0.15 Ω·cm 2 / MPa or less. 2 / MPa or less, The measurement electrolyte solution contains ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L, The nonaqueous electrolyte electricity storage element, wherein the separator has a substrate made of polyolefin.

3. A negative electrode containing silicon or tin and a separator, In the separator impregnated with the test electrolyte, the value (dR / dP) of the resistance increase (dR) relative to the pressure change (dP) when pressure was applied was 0.15 Ω cm 2 / MPa or less, The measurement electrolyte solution contains ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L, The nonaqueous electrolyte electricity storage element, wherein the separator has a shutdown function.

4. A negative electrode containing silicon or tin and a separator, In the separator impregnated with the test electrolyte, the absolute value (|dR / dP|) of the resistance increase (dR) relative to the pressure change (dP) when pressure is applied is 0.005 Ω·cm 2 / MPa or more and 0.15 Ω·cm 2 / MPa or less. 2 / MPa or less, The measurement electrolyte solution contains ethylene carbonate and ethyl methyl carbonate as a solvent and lithium hexafluorophosphate as an electrolyte salt, the volume ratio of the ethylene carbonate to the ethyl methyl carbonate is 30:70, and the concentration of the lithium hexafluorophosphate is 1.0 mol / L, The nonaqueous electrolyte electricity storage element, wherein the separator has a substrate made of polyolefin.

5. 5. The nonaqueous electrolyte storage element according to claim 1, wherein the separator has an air resistance of 250 seconds / 100 mL or less.

6. 6. The nonaqueous electrolyte storage element according to claim 1, wherein the separator contains a resin having a glass transition point of 200[deg.] C. or lower.

7. 4. The nonaqueous electrolyte storage element according to claim 1, wherein the separator comprises a polyolefin.

Citation Information

Patent Citations

  • Tin-based double oxide

    JP2002121023A

  • Microporous film made of polyolefin

    JP2007262203A

  • Nonaqueous electrolyte secondary battery

    JP2009043715A

  • Nonaqueous electrolyte secondary battery, and separator

    JP2011138762A

  • Negative electrode active material layer for lithium ion secondary battery, lithium ion secondary battery, negative electrode mixture for lithium ion secondary battery, and method for producing negative electrode active material layer for lithium ion secondary battery

    JP2014120459A